2013
DOI: 10.5455/vetworld.2013.156-158
|View full text |Cite
|
Sign up to set email alerts
|

Studies on certain quality attributes of meat pickle prepared from spent chicken

Abstract: Aim: An attempt was made to develop a desirable meat pickle from the less tender and low demand spent chicken meat with the prime objective of its better marketability and wider acceptability amongst the non-vegetarian masses. Materials and Methods: Lean of culled spent meat was marinated for overnight and then pressure cooked and fried with spices and condiments to prepare a shelf stable meat pickle. Proximate composition, pH, TBA Values, Total viable plate count, Counts for yeast and moulds and sensory quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
(1 reference statement)
2
9
0
Order By: Relevance
“…Originally the pH value of the chicken pickle was 4.65 which increased somewhat, that is to 4.75 during storage (Table 4). Such trend is observed also by Das et al, (2007), Maiti et al,(2009) andDas et al, (2013).…”
Section: Figure 1 Sensory Test Scores For Chicken Meat Picklesupporting
confidence: 77%
See 2 more Smart Citations
“…Originally the pH value of the chicken pickle was 4.65 which increased somewhat, that is to 4.75 during storage (Table 4). Such trend is observed also by Das et al, (2007), Maiti et al,(2009) andDas et al, (2013).…”
Section: Figure 1 Sensory Test Scores For Chicken Meat Picklesupporting
confidence: 77%
“…The excess oil was drained off. Type of spices used, their preliminary preparation like peeling and grinding, and the amounts of prepared spices taken followed the method of Kanagaraju and Subramanian (2012) and Das et al, (2013) Source: Kanagaraju and Subramanian (2012), Das et al, (2013) The spices were mixed and fried in the drain oil. The spices, salt, MSG and vinegar were mixed with meat and the pickle was filled in clean dry glass jar up to the neck.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proximate characteristics of the meat spread developed were in agreement with the reports of Das et al . [ 17 ]. The pH of the meat spread ranged from 6.43±0.01 to 6.21±0.01 in the entire study period and its value showed a descending progression.…”
Section: Resultsmentioning
confidence: 99%
“…In the third possible mechanism salt ionizes and the ions diffuse into microbial cells and interfere with the metabolism. a. Sensory Analysis The raw formulation of the spices were taken from the (Das, Nath, Hazarika, & Laskar, 2013). The recipe was for the chicken meat pickle and it was not used to make the spicy snacks so further change in the spice recipe was done.…”
Section: Fig: 1 Peroxide Value Analysis Of Snacks Within Different Stmentioning
confidence: 99%